Percepção ambiental dos moradores sobre o loteamento Nova Ituiutaba I e III no município de Ituiutaba-MG - Silva, Silvanio de Cássio da (2019)
Environmental perception is understood as an awareness of the human being, so that, perceiving the environment in which it is inserted, learn to protect it and take care of it in the best way possible. In cities, caring for the environment and providing the urban population with a good and lasting quality of life has become one of the main challenges for public managers, whose confrontation imposes the need to develop popular housing programs that consider in their framework, in addition to housing, the creation and maintenance of healthy environments. The understanding of this dynamics imposes, besides the analysis of the physical apparatus of the dwelling, aspects of the subjectivity that, in the majority, are not considered in the execution of the housing projects. In this context, this study aims to identify the environmental perception of the inhabitants of the Nova Ituiutaba I and III subdivision, in the city of Ituiutaba-MG. In order to do so, a bibliographical review on the theme involving the legal aspects of the legislation on housing and environment, popular housing and environmental perception was elaborated. Subsequent collections of secondary data were carried out in public agencies on the project, field work for the collection of socioenvironmental data, followed by the application of a semi-structured questionnaire with the residents. 269 residences were visited, corresponding to 25% of the number of dwellings. The data produced were organized into spreadsheets, spatialized in the form of maps. Data analysis showed that, in terms of affectivity, most of the residents still did not identify themselves as the new place of residence. The quality of the dwellings, the precariousness of the infrastructure, the deficiency in services, the great distance from the center are pointed out, as well as the feeling of not belonging to the place, as the main cause of the feeling of being forgotten by the public power. In relation to the environment, the residents do not perceive the environmental impacts caused by everyday life in the development and do not identify themselves as agents responsible for them, making clear the crystallization of the idea that environmental quality improvement is the responsibility of public administration, passive agents in the creation and maintenance of healthy environments.